THE REALITY OF LIVING PEOPLE IN URBAN CAN THO CENTURY XX THROUGH AN HA NEWSPAPER - Du, Võ Thanh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
An Ha (1916-1933?) Was the first newspaper written in Quốc ngữ on the land of Cần Thơ at the beginning of the twentieth century. An Ha Newspaper was founded by patriotic intellectuals who wanted to reform the country through business and trade, and to raise people's intellectual standards. Therefore, An Ha newspaper plays an important position in the struggle and raising the intellectual level by the legal form of colonial people to the ruling government through the “freedom” of speech, dissemination, and distribution. Artistic literature medal in Can Tho in particular and the Southwest region in general. The article shows the realistic features of the economic, cultural, and spiritual life of people in Can Tho urban area in the first half of the twentieth century through the news in An Ha newspaper.